The Evaluation of Substrates and Trichoderma sp. Isolates for Cellulase Production - Eka Triwahyuni; Yosi Aristiawan; Novita Ariani; Haznan Abimanyu; Trisanti Anindyawati (Jurnal Kimia Terapan Indonesia, 2018)
AbstractAs higher interest was on the lignocellulose-based or second generation bioethanol production, the research was then more focused on the production of cellulase, especially on the domestic enzyme. Trichoderma sp. is considered as one of the most efficient producer of cellulase. This study was conducted to investigate the performance of Trichoderma sp. on a variety of substrates to produce cellulase. Three types of substrate variations and three types of Trichoderma sp. were used in this experiment. The substrate used were wheat bran, rice bran and oil palm empty fruit bunches (EFBs), whereas Trichoderma sp. isolates were encoded as T004, T051 and T063. Production of cellulase was made by solid fermentation for 7 days. The analysis of cellulase activity was done by National Renewable Energy Laboratory (NREL) method for filter paper assay. The results showed that the type of substrate affected the performance of Trichoderma sp. All types of fungus produced cellulase on wheat bran substrate with activity of 0.52 FPU /ml for T004, 0.23 FPU/ml for T051 and 0.27 FPU /ml for T063. With the rice bran substrate and EFBs, only T004 could produce cellulase and the enzyme activity analyzed were 0.08 FPU /ml and 0.008 FPU/ml respectively. Optimation of the buffer addition on enzyme extraction process produces the highest activity 0.85 FPU/mL for T004 with wheat bran substrate.Â Keywords: cellulase, EFBs, rice bran , Trichoderma sp. , wheat bran